Use Of Traditional and NonTraditional Teaching Methods and Brainstorming Methods in Elementary School Classes - Bobomurodov Kupaysin Abduvayitovich; Raxmonov Bahodir Abduhomidovich (Genius Publishing Group, 2024)
In this article, the use of traditional and non-traditional teaching methods and brainstorming methods in the educational process is very necessary, and the current tasks are covered. Therefore, primary school teachers are a qualified profession. The role and importance of these necessary teaching styles and methods in the training of teachers is extremely high.
Keywords: Traditional; Non-traditional; passive; interactive training